Peran Sharia Venture Capital Corporation dan Venture Debt Corporation terhadap Usaha Mikro, Kecil, dan Menengah di Indonesia - Umam, Khotibul; Tama, Berlian Widya (UI Scholars Hub, 2025)
The limited number of Sharia-compliant venture capital companies results in restricted access for Micro, Small, and Medium Enterprises (Usaha Mikro, Keci, dan Menengahl/UMKM) to alternative funding sources. This limitation may also stem from a lack of literacy regarding Islamic economics and finance among venture capital business players and the broader business community. Therefore, it is necessary to examine the implementation of Sharia Principles within the framework of Venture Capital Corporations (VCC) and Venture Debt Corporations (VDC), as well as the expected role of VCC and VDC in the development of UMK in Indonesia. The findings indicate that both VCC and VDC have applied Sharia principles through agreements that align with their respective characteristics. In addition to providing capital, VCC and VDC are also expected to play a role in offering management support and strategic guidance to UMKM.